Healthy Eating: Improve Nutrition with SNAP - Linda B. Bobroff (EDIS)
SNAP helps people with limited resources buy healthy foods. The U.S. Department of Agriculture (USDA) provides this program to eligible persons of all ages. Learn more in this revised 1-page fact sheet that was written by Linda B. Bobroff and published by the UF Department of Family, Youth and Community Sciences, September 2011.